If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2t + 9) = -18 Reorder the terms: -6(9 + 2t) = -18 (9 * -6 + 2t * -6) = -18 (-54 + -12t) = -18 Solving -54 + -12t = -18 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -12t = -18 + 54 Combine like terms: -54 + 54 = 0 0 + -12t = -18 + 54 -12t = -18 + 54 Combine like terms: -18 + 54 = 36 -12t = 36 Divide each side by '-12'. t = -3 Simplifying t = -3
| 4(f-4)=-24 | | 22+(-8)+32-(12)+8= | | 6(3s+6)=126 | | 8(2l+6)=176 | | 5(a-4)=55 | | (q-7)*6=18 | | 6n^4+15n^3+10n^2-1=0 | | 1-x=3/5 | | 6x-3x=0 | | 3x-24=x+112 | | 6n^5+15n^4+10n^3+29n=0 | | 5x-5x=0 | | x/5=-1/10 | | 25x(x+1)=0 | | 4(n-3)-2n=3 | | 6+35x=15x+22 | | -5(3n+4)=15 | | 6n^3+9n^2+n-1=0 | | 3/11=y/7 | | 13/10=2x/10-1x | | y^2-12y+14=0 | | 28-8x+10x=20-6x+8x | | 4x-19=3x+9 | | -9=u-2 | | 12k+6k^2+k^3+8=64 | | 3a+3=5s-7 | | x(x-3)(x-3)=4.8 | | Cos(2x)-3cos(x)-1=0 | | x=3-28 | | 3f-6=2t+2 | | 2i-3=i+14 | | 4x+5=-2x+5 |